Effects of Metal Oxide Nanoparticle Catalysts on the Diameter of Carbon Nanotubes Produced Via Pulsed Laser Ablation Deposition Technique - Waje, Samaila Bawa (2007)
In this research work, bismuth oxide (Bi2O3) and nickel oxide (NiO) nanoparticles were synthesized through precipitation method, while iron oxide (Fe2O3) nanoparticles were synthesized via citrate pyrolysis. All the as-prepared metal oxide nanoparticles were used as catalysts for the growth of carbon nanotubes via pulsed laser ablation deposition (PLAD) technique. Pellets were first prepared from a mixture of 90 wt% graphite and 10 wt% catalysts in each case, and used as a target. An Nd: YAG laser with wavelength of 532nm and power of 10.24W was used to ablate the target materials, using a frequency of 5 kHz and current of 25A. The target materials were evaporated and transported to the substrate under the influence of argon. The expelled carbon precipitated and diffuses through the metal oxide catalysts and condensed on the substrate as carbon nanotubes. The effect of each of the catalyst on the diameter of the as-grown carbon nanotubes was investigated and the correlation between the type and the particle size of the catalysts and the diameter of the grown CNTs were studied. The results show that, there is a strong correlation between the diameter of the starting catalyst, with the diameter of the resulting carbon nanotubes for both Bi2O3 and Fe2O3, indicating that both catalysts serve as the nucleation point for the CNTs growth. However, the case of NiO shows a significant difference, as the diameter of the as-grown CNTs was eight times bigger than the size of the starting catalyst. This can be attributed to the aggregation of the as-prepared NiO particles to form bigger clusters, consequent to the ablation process. Bamboo-like CNTs were observed for Fe2O3 and NiO, which is attributed to the high cooling rate of the reaction chamber. Further contribution to this structure is the large pulse-to-pulse width of the system (140ns). However CNTs catalyzed by Bi2O3 were defect free tubes which can be attributed to the lower melting point of Bi2O3 compare to other catalysts used, thus forming CNTs at a lower eutectic temperature. From the results, it can be concluded that, for applications that requires a short tube with relatively large diameter Bi2O3 is the best catalyst. For long CNTs with relatively large diameter for encapsulation purposes, NiO is the best catalyst, while Fe2O3 was seen to be the best catalyst for catalyzing CNTs with a narrow diameter.